Cultural adaptation of two school-based smoking prevention programs in Bogotá, Colombia. Issue 8 (26th April 2021) - Sánchez-Franco, Sharon; Arias, Luis Fernando; Jaramillo, Joaquin; Murray, Jennifer M; Hunter, Ruth F; Llorente, Blanca; Bauld, Linda; Good, Sally; West, Judith; Kee, Frank; Sarmiento, Olga L
Abstract: Smoking prevention among adolescents is a public health challenge that is even more significant in low- and middle-income countries where local evidence is limited and smoking rates remain high. Evidence-based interventions could be transferred to low- and middle-income country settings but only after appropriate cultural adaptation. This paper aims to describe the process of the cultural adaptation of two school-based smoking prevention interventions, A Stop Smoking in Schools Trial and Dead Cool, to be implemented in Bogotá, Colombia. A recognized heuristic framework guided the cultural adaptation through five stages. We conducted a concurrent nested mixed-methods study consisting of a qualitative descriptive case study and a quantitative pre- and post quasi-experiment without a control. Contextual, content, training, and implementation modifications were made to the programs to address cultural factors, to maintain the fidelity of implementation, and to increase the pupils' engagement with the programs. Modifications incorporated the suggestions of stakeholders, the original developers, and local community members, whilst considering the feasibility of delivering the programs. Involving stakeholders, original program developers, and community members in the cultural adaptation of evidence-based interventions is essential to properly adapt them to the local context, and to maintain the fidelity of program implementation.